The influence of a fentanyl and dexmedetomidine combination on external respiratory functions in acute hemorrhage model - Nikolay G. Vengerovich; Michael A. Yudin; Alexander S. Nikiforov; Georgiy S. Sagalov; Elina A. Ruzanova; Natalya V. Shperling; Alexander I. Vengerovskii; Igor A. Shperling; Alexander S. Makacheev (Бюллетень сибирской медицины)
Background. The synthetic opioid analgesic fentanyl is widely used for prophylaxis and therapy of traumatic shock associated with massive bleeding. Its side effects – skeletal muscle rigidity and respiratory center depression – are especially pronounced with repeated administration. It is rational to apply fentanyl in diminished doses in combination with non-opioid analgesics in order to reduce respiratory disturbances risk.Aim. The aim of the work is to justify the influence of opioid analgesic fentanyl and α2 -adrenomimetic dexmedetomidine combination on external respiratory functions in acute hemorrhage model.Materials and methods. Acute loss of 35–40% of circulating blood volume was modeled in experiments on 75 white mongrel male rats. The external respiratory functions (respiratory rate, respiratory volume, breath volume per minute) were estimated in animals of 5 groups: 1 – rats without analgesic help (controls); 2–3 – rats receiving a single fentanyl intramuscular injection (ED99 98,96 mcg/kg) or fentanyl together with dexme detomidine (ED99 of combination 67,94 mcg/kg) 15 min after acute blood loss; 4–5 – rats receiving the same drugs 15 min, 30, 45 and 60 min later.Results. In experimental acute loss of 35–40% of circulating blood volume, 15 min later a secondary acute respiratory failure developed with a drop of respiratory rate, respiratory volume and volume of breath per minute by 30%, 21 and 47% (p < 0,05). The external respiratory functions recoverеd after 4 h mainly due to the increase of respiratory volume. A single intramuscular injection of fentanyl caused respiratory depression 15 min after experimental blood loss which resulted in the decrease of breath volume per minute to 30–61% (p < 0,05) for 90 min. Four intramuscular injections of fentanyl 15 min, 30, 45 and 60 min after hemorrhage caused a severe respiratory dysfunction, accompanied by apnea periods and Biot’s respiration. Respiratory rate was reduced to 45–60%, breath volume per minute – to 21–44% (p < 0,05). The respiration improved after 24 h. The addition of central α2 -adrenomimetic dexmedetomidine to the analgesic therapy with fentanyl reduced respiratory depression with the decrease of breath volume to 37–62% (p < 0,05) and an earlier, after 4 h recovery.Conclusion. The repeated injections of fentanyl in diminished dose together with dexmedetomidine in experimental acute hemorrhage caused a pronounced analgesic effect with lower than in fentanyl alone respiratory depression.